God-Conscious AI: Maqasid al-Shari'ah in Algorithmic Design - Ma'rifatun Nikmah; Nasikhin (Salam Institute Islamic Studies, 2025)
This research aims to analyze ethical challenges in the use of artificial intelligence (AI) through the perspective of Islamic philosophy with a focus on the principles of 'adl, taklif, and karamah insaniyyah. This study made a significant contribution by developing an ethical framework based on maqasid al-shari'ah that emphasizes the protection of five fundamental aspects: religion (din), soul (nafs), intellect (aql), heredity (nasl), and property (mal). The research method used is qualitative with a critical literature study approach, which combines the analysis of classical and contemporary Islamic philosophical texts with the discourse of cutting-edge technological ethics. The results of the study show that the maqasid al-shari'ah approach is effective in addressing contemporary challenges such as dehumanization, algorithmic bias, and AI accountability. The findings of the study reveal that Islamic principles are not only relevant but also capable of providing holistic solutions that combine technological advances with spiritual values. This study also succeeded in formulating an AI development model based on social justice and a balance between technological innovation and human rights protection. The conclusion of the study confirms that the Islamic philosophical approach offers an alternative paradigm that is able to balance technological advances with divine and humanitarian values, while providing comprehensive ethical solutions for the responsible development of AI.